Social Network Analysis (SNA) applied to current issues. Guidelines for its implementation in research and management projects - Teves, Laura; Cueto, Jorge Julián (AWARI, 2020)
Social Network Analysis (SNA) has become the most demanded relational approach in the field of basic science and applied science in the last 20 years. Researchers and professionals from traditional social, natural, and exact disciplines agree on the interest in what some identify as the paradigm across the field of traditional sciences problems. While SNA deepens and grows in its developments, analysis, and tools, the demand for courses of graduate and postgraduate academic training increases; as well as the instances of professional updating in both public and private development and management sectors. Based on the supposition that both sectors are related with research work trajectories rooted in institutional and current issues, in this work we aim to present the basic guidelines of our strategies for putting together courses about SNA. Considering three levels based on epistemological, methodological, and transference criteria for the resolution of problems, we propose five lines to be taken into consideration in order to know, develop and apply relational research. The procedures for the design of tools that will allow the collection and construction of databases or the identification of appropriate information for a study of SNA. The analytical path must be explained both in its complexity of combined methods and in the strategies for the identification of patterns as well as the construction of models. Finally, the problems and study frameworks, the research procedures, and the transference instances can be controlled and assessed by testing results and model approximation. Academic and professional training courses provide tools for the appreciation of SNA conceptual fields together with the approximation and delimitation of feasible empiric problems to be studied by SNA.